Pricing of Basket CDS with Stochastic Interest Rates - Wu, Jiaxing (Journal of Global Economy, Business and Finance, 2025)
This paper investigates the pricing of basket credit default swaps (CDS) under stochastic interest rates using a reduced-form model. We assume the default intensity of reference entities and stochastic interest rates both follow Vasicek processes, with risk-free counterparties. Through PDE and ODE methods, we derive approximate closed-form solutions for the joint survival probability density and the probability density of first-default events among reference entities.